Recombinant DNA technology and click chemistry: a powerful combination for generating a hybrid elastin-like-statherin hydrogel to control calcium phosphate mineralization - Misbah, Mohamed Hamed; Santos, Mercedes; Quintanilla, Luis; Günter, Christina; Alonso, Matilde; Taubert, Andreas; Rodríguez-Cabello, José Carlos (Beilstein Journal of Nanotechnology, 2017)
Understanding the mechanisms responsible for generating different phases and morphologies of calcium phosphate by elastin-like recombinamers is supreme for bioengineering of advanced multifunctional materials. The generation of such multifunctional hybrid materials depends on the properties of their counterparts and the way in which they are assembled. The success of this assembly depends on the different approaches used, such as recombinant DNA technology and click chemistry. In the present work, an elastin-like recombinamer bearing lysine amino acids distributed along the recombinamer chain has been cross-linked via Huisgen [2 + 3] cycloaddition. The recombinamer contains the SNA15 peptide domains inspired by salivary statherin, a peptide epitope known to specifically bind to and nucleate calcium phosphate. The benefit of using click chemistry is that the hybrid elastin-like-statherin recombinamers cross-link without losing their fibrillar structure. Mineralization of the resulting hybrid elastin-like-statherin recombinamer hydrogels with calcium phosphate is described. Thus, two different hydroxyapatite morphologies (cauliflower- and plate-like) have been formed. Overall, this study shows that crosslinking elastin-like recombinamers leads to interesting matrix materials for the generation of calcium phosphate composites with potential applications as biomaterials.
Keywords: calcium phosphate; elastin-like recombinamers; hydroxyapatite; mineralization; SNA15